Crank: Crank Series #1 - Hopkins, Ellen (New York : Simon Pulse, 2004)
Seventeen-year-old Kristina Snow is introduced to crank on a trip to visit her wayward father. Caught up in a fast-paced, frightening, and unfamiliar world, she morphs into "Bree" after she "shakes hands with the monster." Her fearless, risk-taking alter ego grows stronger, "convincing me to be someone I never dreamed I'd want to be." When Kristina goes home, things don't return to normal. Although she tries to reconnect with her mother and her former life as a good student, her drug use soon takes over, leaving her "starving for speed" and for boys who will soon leave her scarred and pregnant. Hopkins writes in free-verse poems that paint painfully sharp images of Kristina/Bree and those around her, detailing how powerful the "monster" can be. The poems are masterpieces of word, shape, and pacing, compelling readers on to the next chapter in Kristina's spiraling world. This is a topical page-turner and a stunning portrayal of a teen's loss of direction and realistically uncertain future.
Keywords: Cocaine abuse -- Fiction; Drug abuse -- Fiction; High schools -- Fiction; Schools -- Fiction; Family problems -- Fiction; Pregnancy -- Fiction